2019
DOI: 10.1093/bib/bbz072
|View full text |Cite
|
Sign up to set email alerts
|

New insights on human essential genes based on integrated analysis and the construction of the HEGIAP web-based platform

Abstract: Essential genes are those whose loss of function compromises organism viability or results in profound loss of fitness. Recent gene-editing technologies have provided new opportunities to characterize essential genes. Here, we present an integrated analysis that comprehensively and systematically elucidates the genetic and regulatory characteristics of human essential genes. First, we found that essential genes act as ‘hubs’ in protein–protein interaction networks, chromatin structure and epigenetic modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 90 publications
5
55
0
Order By: Relevance
“…Proteins encoded by such genes are associated with vital molecular functions and are under strong purifying selection. It had been observed that the pathogen-interacting proteins comprise a higher proportion of essential proteins, which however, maybe due to their enrichment among hubs 10 , 28 . Moreover, when we considered hub and nonhub proteins separately, the pathogen-interacting proteins were found to be enriched in essential proteins for both groups, suggesting that these deadly pathogens may disrupt vital functions of the host, thereby facilitating pathogenicity and disease progression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins encoded by such genes are associated with vital molecular functions and are under strong purifying selection. It had been observed that the pathogen-interacting proteins comprise a higher proportion of essential proteins, which however, maybe due to their enrichment among hubs 10 , 28 . Moreover, when we considered hub and nonhub proteins separately, the pathogen-interacting proteins were found to be enriched in essential proteins for both groups, suggesting that these deadly pathogens may disrupt vital functions of the host, thereby facilitating pathogenicity and disease progression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of essential plant genes can help our understanding of key processes such as photosynthesis [78], and assign potential functions to uncharacterized genes. As research in bacteria and yeast [25,27] showed that core genes are more likely to be essential, future pangenome studies can be coupled with integrative analysis of multi-omics datasets, using machine learning and CRISPR/Cas9 knock-outs to identify and characterise the functions of essential genes across the tree of life [75,[79][80][81].…”
Section: Identification Of the Essential Core Genomementioning
confidence: 99%
“…Even for the relatively small bacterial genomes, the function of many accessory genes remains unknown, with variable sequences derived from mobile genetic elements making inference about the role of the accessory genome challenging [11,13,15]. Previously methodologies have been developed, aiming to link properties of genes such as expression level, connectivity in biological networks, and sequence conservation to their function [79,81,95]. Similar approaches could be adopted to understand which accessory genes are likely to be functional and have phenotypic effects.…”
Section: Glossarymentioning
confidence: 99%
“…On the one hand, haploinsufficient genes can function as tumor supressors [27]. On the other hand, essential genes tend to be expressed at higher levels in cancer cells than in normal cells [28]. Thus, knowledge about gene essentiality can help prioritize deleterious variants in genetic studies and could help prioritize therapeutic targets in cancer.…”
Section: Introductionmentioning
confidence: 99%